13 1/2 - Barr, Nevada (New York : Vanguard Press, 2009)
In present-day New Orleans, Polly Deschamps finds herself at yet another lonely crossroads in her life until she encounters architect Marshall Marchand, a lifelong bachelor who spends most of his time with his brother Danny. When Polly's two young daughters from her previous marriage are likewise taken with Marshall, she marries him. But then an ominous prediction by a New Orleans tarot card reader proclaims that Polly will murder her husband, and Polly senses that there could be a connection between Marchand and the infamous "Butcher Boy" multiple homicide.
Keywords: Women college teachers -- Fiction; New Orleans (La.) -- Fiction; Mystery fiction